Pendampingan untuk Pencegahan Stunting Di Desa Korleko Selatan - Azwar Rahman; Nia Herlindawati; Larastika Armili; Lalu Guguh Apridho; Laela Maharani; I Gede Arse Dana Putra; Destia Rani; Iriana Hedianto; Silvia Sifti Ningrum; Marco Bastian Lumentah (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2022)
One of the challenges Indonesiaâ€™s recent generations is facing is a form of failure in growth or more frequently called as â€˜stuntingâ€™. This is a condition where a child (also adults) experiences stagnation in growth, resulting a physical condition (in height and weight) which is said to be below average â€“ becomes a context of itâ€™s own if compared with previous generationsâ€™ data, which shows Indonesia as in â€œstunting emergence stateâ€. Happens so caused by several factors, of which are lack of necessary nutrition, mainly in the first 1000 days of life (or up until 2 years of age and since conception), frequently experiencing sickness in those 1000 days, also unaccommodating uterus. That which also makes the secondary causes are environmental health including sanitary, economics, parentsâ€™ poor awareness (especially mothers), and early marriages/pregnancy. Common side effects also found in children are certain cognitive disadvantages, such as low response, lack of problem solving abilities, et cetera. This scientific article will discuss this topic by reffering to data gathered from the teamâ€™s research in South Korleko Village, Haji Port, East Lombok which is also registered as an area with high stunting rate.